The impact of socialisation on graduates' public service motivation - a mixed method study - Waterhouse, Jennifer; Puchala, Naomi; French, Erica (2014)
The need to attract and retain a high calibre cadre of public servants today has resulted in a renaissance of interest in public service motivation (PSM) within public management literature. This article outlines a study of PSM with graduate employees within an Australian public sector. The study extends our understanding of PSM by adopting a longitudinal, mixed method design, including surveys and individual interviews, to consider the effects of socialisation on levels of PSM. Results show an organisation's mission and values do not affect individual PSM while work type and communication style is vital and organisational socialisation can provide a negative influence. Reproduced. 10
Keywords: Civil service; Motivation